Ferroelectric modulation in flexible lead-free perovskite Schottky direct-current nanogenerator for capsule-like magnetic suspension sensor - Jiang, Feng (2023)
The tribovoltaic nanogenerator (TVNG), a promising semiconductor energy technology, displays outstanding advantages such as low matching impedance and continuous direct-current output. However, the lack of controllable and stable performance modulation strategies is still a major bottleneck that impedes further practical applications of TVNG. Herein, by leveraging the ferroelectricity-enhanced mechanism and the control of interfacial energy band bending, a lead-free perovskite-based (3,3-difluorocyclobutylammonium)2 CuCl4 ((DF-CBA)2 CuCl4 )/Al Schottky junction TVNG is constructed. The multiaxial ferroelectricity of (DF-CBA)2 CuCl4 enables an excellent surface charge modulating capacity, realizing a high work function regulation of ≈0.7 eV and over 15-fold current regulation (from 6 to 93 µA) via an electrical poling control. The controllable electrical poling leads to elevated work function difference between the Al electrode and (DF-CBA)2 CuCl4 compared to traditional semiconductors and halide perovskites, which creates a stronger built-in electric field at the Schottky interface to enhance the electrical output. This TVNG device exhibits outstanding flexibility and long-term stability (>20 000 cycles) that can endure extreme mechanical deformations, and can also be used in a capsule-like magnetic suspension device capable of detecting vibration and weights of different objects as well as harvesting energy from human motions and water waves.